Residu Gula Glikokonjugat pada Lambung Depan Kerbau Rawa (Bubalus bubalis) Kalimantan Selatan (SUGAR RESIDU OF GLYCOCONJUGATES IN FORESTOMACH OF SOUTH KALIMANTAN SWAMP BUFFALO (BUBALUS BUBALIS) - Nurliani, Anni; Pitojo, Teguh Budi; Kusindarta, Dwi Liliek (Jurnal Veteriner; Vol 15 No 2 (2014), 2014)
The ability of swamp buffaloes to adapt with swamp environment was suggested to be supported bytheir digestive system efficiency. The research was done to obtain scientific explanation about digestiveefficiency of swamp buffalo by identification on kinds and distribution of glycoconjugates in swamp buffaloforestomach. Six male swamp buffaloes aged more than 2.5 year old and had body weight between 300-400kg were used in this study. Samples were obtained from Regency of Banjar slaughter house, SouthKalimantan. Every parts of the forestomach included rumen, reticulum, and omasum was taken andprocessed for microscopic observation with hematoxyline eosin (HE) and alcian blue-periodic acid schiff(AB-PAS) stainings. Sugar residues of glycoconjugates were localized with lectin histochemistry wheatgerm agglutinin (WGA), ulex europaeus agglutinin (UEA), ricinus communis agglutinin (RCA), concanavalinagglutinin (Con A), and soybean agglutinin (SBA). Every part of swamp buffalo forestomach had kinds ofspecific glycoconjugates with special distribution pattern which were different with other ruminant, andwere suitable for their functions in that part. The existence of D mannose/D glucose glycoconjugates thatwas dominant in forestomach estimated that had important role in supporting fermentative digestionfunction in swamp buffalo, through its function as receptor bacteria attachment. This is suggested as aspecial characteristic in digestive system of swamp buffalo which causes high digestive efficiency inswamp buffalo.
Keywords: glycoconjugates, forestomach, swamp buffalo, lectin